Novel Tools for Ocean Biogeochemical Models - Bardin, Ann Marie (eScholarship, University of California, 2014)
Ocean general circulation models of the IPCC class have biases even when simulatingpresent-day conditions, which may bring into question their predictions of futureconditions. This dissertation is about tools for, and results from assessing biases in theCommunity Earth System Model (CESM) ocean component, by itself and when combinedwith the Biological Ecosystem Cycling (BEC) model. Newly developed tools and theirapplications are listed.1. An offline matrix tracer transport model for the ocean component of CESM.2. A fast Newton-Krylov implicit tracer equilibrium solver for both the annually-averagedand the seasonally-varying circulation.3. An effective preconditioner for the solver simulating radiocarbon. Application results: For a natural radiocarbon simulation, an equilibrium solution was obtained in 23 model-years, a dramatic decrease from the 4000 model-years reported for time-stepping. The modeled circulation in the deep Pacific Ocean produced radiocarbon ages twice those of observations.4. A capability for computing the surface origin of water mass fractions as well as theage of the various water masses. Application results: The North Atlantic was the major supplier of ventilated water to not only the Atlantic, but also the Pacific and Indian Oceans. A lack of formation of bottom water in the Southern Ocean was discovered.5. A capability for restricting the tracer simulation domain to a limited region of theocean while retaining the effectiveness of advection and diffusion fields on theboundary. This reduces computational costs and allows separating local versusremote impacts of tracer sources on the biogeochemical tracer concentrations. Thiscapability has the potential to provide a platform for further biogeochemical studies. Application results: The Indian Ocean region was isolated. Global versus regional circulation effects were determined using radiocarbon. Most of the bias within the region was eliminated by using observational, rather than globally calculated values, on the boundaries. Oxygen production and consumption from a CMIP5 BEC simulation were used to drive a regional oxygen model. Boundary values of oxygen from the CMIP5 BEC simulation were replaced with observations, resulting in less bias within the region. However, significant bias in the location of the Arabian Sea oxygen minimum zone remained.